Математична модель оперативної оптимізації режиму підстанції електричної мережі - Данилюк, О. В.; Бахор, З. М.; Рильський, С. М. (Видавництво Національного університету «Львівська політехніка», 2007)
Decrease of technical power energy losses on substations of electric networks is one of important tasks of their exploitation. The one of ways to solve this task is operative optimization of operation regimes of the substation due to change of amount of working transformers. The mathematical model of operative optimization of the operation regimes of substation, criterion of economical viability of substation transformer disconnecting and method of its determination was considered.